526 ALAGILLE SYNDROME, A CASE REPORT. (15th December 2022) - Nobile, Edoardo; De Filippis, Aurelio; Circhetta, Simone; Bernardini, Federico; Viscusi, Michele; Gallo, Paolo; Ussia, Gian Paolo
Abstract: Alagille syndrome (AGS) is a dominantly inherited multisystem disorder caused by heterozygous mutations of genes that are components of the Notch signaling pathway. The main clinical manifestations of AGS are intrahepatic bile duct paucity, congenital heart defects involving primarily the pulmonary arteries, butterfly vertebrae, anterior chamber defects of the eye and facial dysmorphism. A male patient of 39 years old came to our observation due to the worsening of dyspnea, cyanosis, dizziness, heartbeat and asthenia for about two years. His cardiological history includes percutaneous pulmonary artery angioplasty in both left and right main pulmonary artery in 1994. In 2012, finding of pulmonary hypertension and diagnosis of Alagille syndrome confirmed by genetic analysis (JAG1 gene), and vasoreactivity testing of the pulmonary circulation was positive. Intrastent restenosis of the right lobar pulmonary artery treated with POBA in 2016. Patient therapy includes, diltiazem 60 mg OD, macitentan 10 mg OD, sildenafil 40 mg TID. Echocardiogram showed: preserved global and segmental systolic function. Minimal mitral valve insufficiency. Dilated right ventricle (RV / LV> 1), ipokinetic. Right atrium of increased size. Mild tricuspid valve insufficiency (VD-AD 20 mmHg). reduced systolic flow acceleration time (80 msec). Inferior vena cava of normal caliber with preserved inspiratory collapse. Indirect signs of pulmonary hypertension. The six minutes walking test showed severe desaturation after only one hundred meters. Right catheterization showed severe pulmonary hypertension (PAPm 63 mmHg). blood gas analysis showed oxygen saturation of 83% in the pulmonary artery. Angiography of the pulmonary arteries showed intrastent restenosis on the left pulmonary artery and fracture of the stent on the right pulmonary artery. For which was performed angioplasty with stent intrastent implantation in the right pulmonary artery. After the procedure there was immediate reduction in pulmonary mean arterial pressure (53 mmHg), a progressive improvement in 02 saturation (88% at discharge) while the echocardiogram after the procedure results unchanged except for the increasing of the systolic flow acceleration time (100 msec). Right catheterization showed a gradient trans-stenosis of 96 mmHg. We performed angioplasty with stent intrastent implantation in the right pulmonary artery. After that we saw a drop in the gradient trans-stenosis (63 mmHg) and a raise in the systolic pressure of the left pulmonary artery. In Conclusion, in this particular population of patients with pulmonary hypertension even if on maximal therapy, the worsening of symptoms should in our opinion be an indication for right cardiac catheterization and angiography of the pulmonary arteries.